(3JLQjO GdRhGFO hJbQjH GdahGFOs - (3GdeRLO , CMeO Hf YeQ Hf eMeO GdSjaj GdeOGOj, Uaj GdOjf,J (B930 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ HUGFQ GdUGdMjf ade jJNPhG ChdjGA Ohfg s
(3BNQgG (B:s
(3bdJ de jHjf bOQ GdMGLI ef jhe Ch SfI heG HjfgeG Je GdcJGH HMeO Gdedc GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3GdfSNI HgG MhGTs
(3Hg ebGHdI Ydi jO eGdcg YHO GdQMefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B188 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B34s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B227s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs